Extracellular vesicles in gastric cancer: role of exosomal lncRNA and microRNA as diagnostic and therapeutic targets - Jiang, Chengyao; Zhang, Jianjun; Wang, Wentao; Shan, Zexing; Sun, Fan; Tan, Yuen; Tong, Yilin; Qiu, Yue (Frontiers in Physiology, 2023)
Extracellular vesicles (EVs), including exosomes, play a crucial role in intercellular communication and have emerged as important mediators in the development and progression of gastric cancer. This review discusses the current understanding of the role of EVs, particularly exosomal lncRNA and microRNA, in gastric cancer and their potential as diagnostic and therapeutic targets. Exosomes are small membrane-bound particles secreted by both cancer cells and stromal cells within the tumor microenvironment. They contain various ncRNA and biomolecules, which can be transferred to recipient cells to promote tumor growth and metastasis. In this review, we highlighted the importance of exosomal lncRNA and microRNA in gastric cancer. Exosomal lncRNAs have been shown to regulate gene expression by interacting with transcription factors or chromatin-modifying enzymes, which regulate gene expression by binding to target mRNAs. We also discuss the potential use of exosomal lncRNAs and microRNAs as diagnostic biomarkers for gastric cancer. Exosomes can be isolated from various bodily fluids, including blood, urine, and saliva. They contain specific molecules that reflect the molecular characteristics of the tumor, making them promising candidates for non-invasive diagnostic tests. Finally, the potential of targeting exosomal lncRNAs and microRNAs as a therapeutic strategy for gastric cancer were reviewed as wee. Inhibition of specific molecules within exosomes has been shown to suppress tumor growth and metastasis in preclinical models. In conclusion, this review article provides an overview of the current understanding of the role of exosomal lncRNA and microRNA in gastric cancer. We suggest that further research into these molecules could lead to new diagnostic tools and therapeutic strategies for this deadly disease.